Description of Pain Levels in Postoperative Sectio Caesarea Patients Using, The ERACS Method - Wahyudi, Wahyudi Saputra; Triyudono, Danang; Sebayang, Septian (Java Nursing Journal, 2025)
Background: Postoperative pain management is an essential component of patient care after cesarean section (C-section) because inadequate pain management can negatively affect maternal recovery as well as the psychological well-being of mothers and overall surgical outcomes. Enhanced Recovery After Cesarean Section (ERACS) has been introduced to enhance the care patients receive in the perioperative period concerning reduced pain, improvement in recovery, and decreased opioid dependence. Despite growing adoption, very few studies have reported on the ability of the method to manage post-C-section pain. Purpose: To evaluate the pain experience of postoperative C-section patients managed with the ERACS method in Bunda Medika Jakabaring Hospital. Methods: A cross-sectional descriptive quantitative study was conducted among 66 Cesarean delivery patients treated by the ERACS method from July 20 to August 20, 2024. The purposive sampling method was used to select the subjects, and the pain levels were measured by using the Numerical Rating Scale (NRS). Pain levels were categorized as no pain (0), mild pain (1-3), moderate pain (4-6), or severe pain (7-8). Results: Of the patients, 16 (24.2%) had no pain; 43 (65.2%), had mild pain; 5 (7.6%), were moderate; and 2 (3.0%) had severe pain. Most of the patients (65.2%) noted only mild pain, indicating that ERACS contributes significantly to reducing postoperative pain. Conclusion: These findings indicate that the ERACS method greatly contributes toward minimizing postoperative pain in C-section patients, thus endorsing its use in the clinical setting. Further studies should also consider larger sample sizes and comparative analyses to substantiate these findings and look into other advantages of ERACS in enhancing